Bio-molecule detection for preqnancy sensing using in house fabricated nanostructure based biosenser - Balakrisnan, Sharma Rao (Universiti Sains Malaysia, 2013)
Sharma Rao Balakrishnan has won gold medal at National Research and Innovation Competition (NRIC) 2012, 17th - 19th July 2012 was held at Dewan Utama Pelajar, located at USM Main Campus, Penang, Malaysia.